Mobility planning in cross-border metropolitan regions: the European and North American experiences. Issue 2 (4th March 2022) - Peña, Sergio; Durand, Frédéric
ABSTRACT: This paper investigates the cooperation logics within European and North American cross-border metropolitan regions to explain how institutional actors respond to the challenges of globalization. The focus is on analysing the relationship between concepts of space and planning to provide insights into the way cross-border metropolitan regions are produced, and on how the border is conceived. The hypothesis is that mobility galvanizes stakeholders on both sides of the border in order to undertake collective actions to overcome obstacles posed by an international border, even in situations where the border is conceived as a hard barrier. The study employs a comparative approach of two cross-border regions: Basel (Switzerland/France/Germany) and San Diego–Tijuana (United States/Mexico), according to three dimensions of mobility (airport and pedestrian infrastructures, and daily mobility management). The main conclusion is that although these two border contexts are completely different, similarities exist regarding the planning of mobility, and the space conception. States are willing to relinquish sovereignty allowing a foreign government, cross-border structure or a private company to perform planning operations that normally belong to the nation-states. Furthermore, local authorities do whatever is needed to facilitate the flow of workers and people across borders when economic costs due to border barriers are too high.